On a Flow Reducing Volume Within Hamiltonian Isotopy Class (Journal of Mathematical Study, 2025)
We survey basic properties of the geometric flow for immersions within a Hamiltonian isotopy class and propose a definition for Type I singularities.
Keywords: Higher order flow within Hamiltonian isotopy class; Hamiltonian stationary